Analisis Tingkat Konstribusi Ekspor terhadap Pertumbuhan Ekonomi di Indonesia: Studi Kasus Ekspor Indonesia ke Amerika Serikat Berdasarkan Harmonized System (HS) Code 71 - Ikke Adelia Amanda; Muhammad Yasin (Jurnal Pajak dan Analisis Ekonomi Syariah, 2026)
Exports as a component of international trade contribute significantly to the development and growth of a country’s economy. In Indonesia, export activities are considered one of the key drivers in increasing national economic performance. This research seeks to evaluate the role of Indonesia’s exports to the United States within the Harmonized System (HS) Code 71 commodity classification, encompassing pearls, gemstones, precious metals, and jewelry products, in influencing Indonesia’s economic growth as reflected by Gross Domestic Product (GDP) at constant prices.The analysis focuses on three specific commodity groups: Pearls and Precious Stones (HS 71.01–71.05), Precious Metals and Metals Clad with Precious Metals (HS 71.06–71.12), and Jewelry and Related Articles (HS 71.13–71.18). A descriptive quantitative research design was employed, utilizing secondary time-series data collected for the 2015–2024 period. Data sources included the Indonesian Central Bureau of Statistics (BPS) and Trade Map. To assess the relationship between variables, this study adopted multiple linear regression analysis accompanied by classical assumption testing and hypothesis testing using both t-test and F-test procedures. The empirical findings demonstrate that export performance within the HS Code 71 category underwent considerable fluctuations throughout the observation period, reaching its peak in 2024.Furthermore, the statistical results indicate that each commodity sub-category contributes differently and exerts varying effects on Indonesia’s real GDP, both individually and collectively. The outcomes of this research are expected to provide useful references for government institutions in developing trade cooperation strategies and policy decisions, while also supporting business actors in strengthening the international competitiveness of Indonesian products.